An optimized security solution based on trust value for multithreaded wireless body area network communication. Issue 2 (18th November 2019) - Saha, Sanchari; K. Anvekar, Dinesh
Abstract : Purpose: Security of wireless body area network communication is highly important as it directly impacts human life. This paper aims to focus on battlefield application area of WBAN for implementing security where data must be protected against various possible attacks before delivering over a public network. Design/methodology/approach: Providing a strong security system is still a research challenge due to low computational power of used sensors for protecting transmission data. In this paper, the authors have proposed an optimized security solution for multithreaded wireless body area network (MWBAN) using trust-based distributed group key management technique to overcome the drawbacks of existing elliptical curve cryptography-homomorphism (ECC-Homomorphism) scheme as well as coded cooperative data exchange group key management (CCDE_GKM) scheme. Findings: The proposed optimized security solution is implemented for a particular deployment strategy and test runs are conducted. It is found that when number of attack nodes increased to 25, compared to ECC–Homomorphism and CCDE_GKM for the proposed trust-based distributed group key management technique there is an improvement in performance parameters such as throughput is dropped to only 10.11 Kbps, average delay is just 3.4 s, energy consumption is maximum 29 joules, packet loss is only 12.3 per cent, 90.9 per cent truly can detect attack, only 8.9 per cent false attack detection and 84 per cent true negative detection. Social implications: Medical care can be provided to human beings with much ease and flexibility via remote monitoring. The user can be at any place, can do his/her everyday work while remotely being monitored of their health parameters and secured transmission of their data to the health-care center for medical service in need. Originality/value: This paper presents an optimized security solution for MWBAN using trust-based distributed group key management technique where bilinear pairing theory is used as major cryptographic base. Optimal key is selected based on trust value and also attack nodes are detected based on trust value to control participation in communication.